2009
DOI: 10.1007/s00464-009-0595-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes after inguinal hernia treatment: a reason for chronic pain and recurrent hernia?

Abstract: The treatment of inguinal hernia by the suture technique is followed by significant anatomical changes such as reduction of the surface area and a subsequent increase of tension in the inguinal region. This could be one of the main reasons for chronic pain and hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several studies have investigated postoperative pain after hernia repair [16][17][18]. Fei et al [19] reported the feasibility of primary inguinal repair with open tension-free and sutureless technique using a new polypropylene ''patch and plug system'' (Prolene 3D patch).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated postoperative pain after hernia repair [16][17][18]. Fei et al [19] reported the feasibility of primary inguinal repair with open tension-free and sutureless technique using a new polypropylene ''patch and plug system'' (Prolene 3D patch).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inXammation and foreign body reaction are other important factors causing POP in hernia surgery [21]. Despite being a biocompatible material, polypropylene is not absorbable.…”
Section: Discussionmentioning
confidence: 99%
“…The reported follow‐up was sufficient for detection of recurrence in all analysed trials ( Table 1 ), all employed intention‐to‐treat methodology and the analysis of this important outcome measure may be considered robust in the absence of statistical evidence of bias or heterogeneity. Patient‐related risk factors including changes in anatomy after index hernia repair18, or surgeon‐related factors including the greater likelihood of technical error17, increase the likelihood of recurrence independently of the operative technique employed for the repair of recurrent inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%